2013
DOI: 10.1161/circulationaha.112.000756
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Adrenomedullin-RAMP2 System Is Essential for Vascular Integrity and Organ Homeostasis

Abstract: Background-Revealing the mechanisms underlying the functional integrity of the vascular system could make available novel therapeutic approaches. We previously showed that knocking out the widely expressed peptide adrenomedullin (AM) or receptor activity-modifying protein 2 (RAMP2), an AM-receptor accessory protein, causes vascular abnormalities and is embryonically lethal. Our aim was to investigate the function of the vascular AM-RAMP2 system directly. Methods and Results-We generated endothelial cell-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 45 publications
7
82
0
Order By: Relevance
“…We previously showed that RAMP2 is essential for angiogenesis and vascular homeostasis in both embryos and adults [17,18]. In the present study, we found that the phenotypes of RAMP2−/− and RAMP3−/− mice are strikingly different: whereas RAMP2−/− mice die in utero due to vascular abnormalities, RAMP3−/− mice are born normally with no blood vessel or lymphatic abnormalities.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…We previously showed that RAMP2 is essential for angiogenesis and vascular homeostasis in both embryos and adults [17,18]. In the present study, we found that the phenotypes of RAMP2−/− and RAMP3−/− mice are strikingly different: whereas RAMP2−/− mice die in utero due to vascular abnormalities, RAMP3−/− mice are born normally with no blood vessel or lymphatic abnormalities.…”
Section: Discussionsupporting
confidence: 51%
“…More recently, we developed drug-inducible vascular endothelial cell-specific RAMP2−/− (DI-VE-RAMP2−/−) mice, with which we can induce RAMP2 gene deletion in adults. Using this model, we found that RAMP2 is essential for angiogenesis and vascular homeostasis in adults, as DI-VE-RAMP2−/ − mice exhibit vascular structural abnormalities and spontaneously develop vascular inflammation and organ fibrosis [18]. Collectively, these findings indicate that the AM-RAMP2 system is essential for angiogenesis and vascular homeostasis throughout a mouse's life, from embryo to adult.…”
Section: Introductionmentioning
confidence: 73%
“…And RAMP2 À/À embryos also die in utero at midgestation due to severe deformation, vascular fragility, severe edema, and hemorrhage [65]. Very recent studies with endothelial cell-specific RAMP2 KO mice have confirmed that the AM-RAMP2 system is a key determinant of vascular integrity and homeostasis from prenatal stages to adulthood [66]. Surprisingly, a complete absence of RAMP3 has no effect on survival [67].…”
Section: Physiological Activities Of Ammentioning
confidence: 99%
“…Although AM is a vasodilator when injected peripherally, it acts as a vasoconstrictor when it is injected into the brain, through stimulation of sympathetic nervous system [74]. Moreover, AM and PAMP are well known for being potent angiogenic agents [75], they are necessary to maintain the integrity of the microvasculature [66] and promote a faster healing of epithelial wounds [76].…”
Section: Physiological Activities Of Ammentioning
confidence: 99%
“…Ras homolog gene family, member A (RhoA), cell division control protein 42 (Cdc42), and protein superfamily of small GTPases (Ras)-related C3 botulinum toxin substrate 1 (Rac1)-the Rho GTPases-have been implicated in various vascular diseases, such as atherosclerosis, hypertension, diabetes, vascular leakage, angiogenesis, and aneurysm formation (Ferri et al, 2013;Jin et al, 2013;Khan et al, 2013;Koyama et al, 2013;Marinkovic et al, 2013;Nagase, 2013;Boissier and Huynh-Do, 2014;Liu et al, 2014;Sun et al, 2014;Varela et al, 2014). Rac1 is well recognized for its role in actin remodeling and the induction of membrane protrusions, but it also has several other downstream effects, such as activation of NADPH oxidases or cell-surface receptor-mediated signaling resulting in an inflammatory response (Ambriz-Pena et al, 2014;Cuadrado et al, 2014;D'Ambrosi et al, 2014;Marinkovic et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%